Response surface methodology for optimal immobilization of Aspergillus niger ATCC 1015 lipase by adsorption method - Osho, Michael; Popoola, Tope; Adeleye, Tolulope; Adetunji, Christianah (International Journal of Biological Research, 2016)
Optimization of Vegetable Sponge (Luffa aegyptiaca) (VS) - immobilization conditions of Aspergillus niger ATCC 1015 lipase on Solid State Fermentation (SSF) was carried out using Response Surface Methodology (RSM). Four independent variables (temperature, pH, enzyme loading and enzyme stability) were optimized using Central Composite Design of RSM for lipase production in a solid rice bran-physic nut cake medium. The optimal immobilization conditions obtained were 45 Â°C, pH 7.0, 2.5% (w/v) enzyme loading and 32.5% (v/v) enzyme stability (using glutaraldehyde as crosslinking agent) resulted into lipase activity of 98.6 Ug-1. The result demonstrates the potential application of vegetable sponge under SSF system in immobilizing lipase, thus contributed to efficiency of the use of this biomatrix as an immobilizing agent. The statistical tools employed predicted the optimal conditions for the production of the immobilized lipase thus revealing the full potential of the support.